The impact of AI writing tools on the content and organization of students' writing: EFL teachers' perspective - Marzuki,; Widiati, Utami; Rusdin, Diyenti; Darwin,; Indrawati, Inda (Cogent education, 2023)
The primary objective of this study was to examine the range of available Artificial Intelligence (AI) writing tools and assess their influence on student writing, particularly in terms of content and organization, as perceived by English as a Foreign Language (EFL) teachers. Utilizing a qualitative approach, the research was constructed within a case study design. The data was collected via semi-structured interviews, targeting information about the diversity of AI writing tools and their impact on students" writing quality. The study gathered data from four EFL teachers across three distinct universities in Indonesia, shedding light on the variety of AI writing tools used in their classrooms. These included applications like Quillbot, WordTune, Jenni, Chat-GPT, Paperpal, Copy.ai, and Essay Writer. Furthermore, these teachers unanimously agreed that the AI writing tools positively improved their students' writing quality, particularly enhancing the quality of their content and organization. The findings of this study imply that integrating AI writing tools can prove beneficial in elevating the quality of EFL student writing. In response to this study's limitations, recommendations for future research were also addressed.